BERBAGI PENGHASILAN: SISTEM EKONOMI DAN ETOS KERJA KRISTIANI BERDASARKAN PEMBACAAN TRADISI TERHADAP EFESUS 4:28 - Saputra, Jefri Andri (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2023)
This article aims to construct an economic system and a Christian work ethic to overcome the problem of poverty due to economic recession. The author formulate the economic activity and a Christian work ethic by analyzing the text of Ephesians 4:28. The research method used is traditional criticism. The tradition chosen is the tradition of picking up the remaining harvest. The author finds that the transformation in economic activity can support poverty alleviation. This transformation refers to implementing the economic system which solidarity with the poor and several Christian work ethics, namely working hard, doing good and beneficial work, working to be self-sufficient, and working to share.